EMG ACTIVITY OF MUSCLES OF THE CRANIOMANDIBULAR SYSTEM IN SUBJECTS WITH NARROWING UPPER JAW AND POSTERIOR CROSSBITE - L.V. Smaglyuk; P. Echarri; A. V. Liakhovska; M. V. Trofymenko (Проблеми екології та медицини)
Posterior crossbite in children and adolescents has been linked to asymmetrical function and performance of the masticatory muscles. Electromyography (EMG) serves as an objective and widely applicable evidence-based method for diagnosing muscle function. The aim of our study was to analyze electromyographic (EMG) activity of muscles of the craniomandibular system in subjects with a narrowing upper jaw and unilateral posterior crossbite. Material and methods. The first (study) group consisted of 18 subjects with narrow maxilla and unilateral posterior crossbite. 20 age-matched children with normal occlusion were included in the control group. The average age of subjects in the study group was 8.4±1.4 years, in the control group – 8.8±1.6 years. The exclusion criteria of the study were as follows: previous or active orthodontic treatment, clefts, traumas in the maxillofacial region, and general diseases. EMG activity of the anterior temporal, masseter, sternocleidomastoid (SCM), orbicularis oris, and mentalis muscles on both sides (left and right) was recorded during two 30-second tests: maximum voluntary clenching and swallowing a sip of water. Maximum voluntary clenching was performed in the intercuspal position. EMG data were processed using Neurotech's Synapsis software. EMG activity for each muscle was estimated by the maximum amplitude of the muscle contractions (μV). Results. EMG activity in children with narrowing upper jaw and unilateral posterior crossbite of anterior temporal, masseter, and sternocleidomastoid muscles was asymmetrical and differed between the left and right sides. Higher bioelectrical muscle activity was found on the crossbite side for the masseter and anterior temporalis muscle, and on the opposite side – for sternocleidomastoid muscles. Values of maximum amplitude of sternocleidomastoid muscles were higher in the study group than in the control group without significant difference. There was a statistically significant difference in EMG activity of mentalis and orbicularis oris muscles between the two groups of children (p<0.05). Values of EMG activity of mentalis and orbicularis oris were higher in the study group.